2011
DOI: 10.1063/1.3564904
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cross-polarization detection of coupling far-field light to highly confined plasmonic gap modes via nanoantennas

Abstract: Plasmonic coupling effect between two gold nanospheres for efficient second-harmonic generation J. Appl. Phys. 112, 083102 (2012) Controlled spatial switching and routing of surface plasmons in designed single-crystalline gold nanostructures Appl. Phys. Lett. 101, 141114 (2012) Negative and positive photoconductivity modulated by light wavelengths in carbon nanotube film Appl. Phys. Lett. 101, 123117 (2012) Polarizability of supported metal nanoparticles: Mehler-Fock approach

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…2(a) and 3(c)]. This value is in good correspondence with the previously reported result [11] except the fact that in our case the excitation spot area is 8 times larger. With the bottom and bottom-and-side reflectors the coupling efficiency is 24% and 26%, respectively [ Figs.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…2(a) and 3(c)]. This value is in good correspondence with the previously reported result [11] except the fact that in our case the excitation spot area is 8 times larger. With the bottom and bottom-and-side reflectors the coupling efficiency is 24% and 26%, respectively [ Figs.…”
supporting
confidence: 82%
“…Optical antennas have been used for fluorescence enhancement and sensing [5], light-emitting diodes [6], lasers [7], photodiodes [8], and solar cells [9], but only recently have nanoantennas been applied to coupling [10][11][12]. In the abovementioned works [10][11][12] dipole or bowtie antennas were used. The maximal reported coupling efficiency (CE), which is the ratio of the power launched into the waveguide to the incident power, of the antenna system [11] for telecom wavelength 1.55 μm was about 15%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, prototype nanocircuits using gap nanoantennas [5,6] in connection with plasmonic two-wire transmission lines (TWTLs) have been theoretically proposed [7][8][9] and experimentally studied [10][11][12], showing a realizable approach to the manipulation of electromagnetic field for enhanced spectroscopy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that CE can be increased to 26% by using additional reflectors [20]. Experimentally measured CE was 15% [21]. optical devices and systems ются в плазмонном волноводе.…”
Section: Iods On the Basis Of Nanoantennasmentioning
confidence: 99%